NEW APPROACHES TO TEACHING ENGLISH: GIVE THE PUPILS WHAT THEY WANT! - Kamola Mahmudova; Parvina Kholikova (Journals Park Publishing, 2023)
This article aims to clarify in what sense there is awareness about using new technologies, their activities and their applications in language classrooms. The methods are discussed and compared with each other in order to reach a general opinion. This article focused on the effects of using techniques applied during English lessons in high methodology style.
Keywords: The audio-lingual, communicative approach, task-based approach, large-scale production, evaluation criteria, overarching project, enable students’ communication, smartphones enhance.